Sphaeropsis sapinea and Associated Endophytes in Scots Pine: Interactions and Effect on the Host Under Variable Water Content - Blumenstein, Kathrin; Bußkamp, Johanna; Langer, Gitta Jutta; Schlößer, Rebekka; Parra Rojas, Natalia Marion; Terhonen, Eeva (Frontiers in Forests and Global Change, 2021)
The ascomycete Sphaeropsis sapinea is the causal agent of the Diplodia Tip Blight disease on pines and other conifer species. This fungus has a symptomless endophytic life stage. Disease symptoms become visible when trees have been weakened by abiotic stress, usually related to warmer temperatures and drought. Currently, this disease is observed regularly in Scots pine (Pinus sylvestris) sites in parts of Europe, such as Germany, increasing dramatically in the last decade. Changes in climatic conditions will gradually increase the damage caused by this fungus, because it is favored by elevated temperature. Thus, host trees with reduced vitality due to climate change-related environmental stress are expected to be more susceptible to an outbreak of Diplodia Tip Blight disease. There is currently no established and effective method to control S. sapinea. This project aims to reveal the nature of the endophyte community of Scots pine. Utilizing the antagonistic core community of endophytes could serve as a novel tool for disease control. Results from this study provide a starting point for new solutions to improve forest health and counter S. sapinea disease outbreaks. We screened potential antagonistic endophytes against S. sapinea and infected Scots pine seedlings with the most common endophytes and S. sapinea alone and combination. The host was stressed by limiting access to water. The antagonism study revealed 13 possible fungi with the ability to inhibit the growth of S. sapinea in vitro, for example Sydowia polyspora. None of the tested co-infected fungi (Desmazierella acicola, Didymellaceae sp., Microsphaeropsis olivacea, Sydowia polyspora, and Truncatella conorum-piceae) showed strong necrosis development in vivo, even when host stress increased due to drought. However, the infection experiment demonstrated that drought conditions enhance the effect of the disease outbreak, triggering S. sapinea to cause more necrosis in the infected twigs.